2017
DOI: 10.1155/2017/6138424
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Injury and Recovery after Hypertensive Intracerebral Hemorrhage

Abstract: Hypertensive intracerebral hemorrhage (ICH) could very probably trigger white matter injury in patients. Through the continuous study of white matter injury after hypertensive ICH, we achieve a more profound understanding of the pathophysiological mechanism of its occurrence and development. At the same time, we found a series of drugs and treatment methods for the white matter repair. In the current reality, the research paradigm of white matter injury after hypertensive ICH is relatively obsolete or incomple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 78 publications
0
30
0
Order By: Relevance
“…Brain neuroinflammation occurs after experimental ICH and causes secondary brain injury, including brain edema, neuronal death, brain atrophy, and poor neurological outcomes . WM injury, known to be a frequent complication of ICH, is one consequence of the inflammatory response induced by blood components and metabolites . The present study showed that minocycline confers protection against hemorrhagic WM injury in a mammal model and discovered a potential mechanism for this protection via the TGF‐β/MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Brain neuroinflammation occurs after experimental ICH and causes secondary brain injury, including brain edema, neuronal death, brain atrophy, and poor neurological outcomes . WM injury, known to be a frequent complication of ICH, is one consequence of the inflammatory response induced by blood components and metabolites . The present study showed that minocycline confers protection against hemorrhagic WM injury in a mammal model and discovered a potential mechanism for this protection via the TGF‐β/MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, WM injury reflects the brain's vulnerability to further insult and predicts poor outcomes after ICH. [4][5][6] Our previous work has shown that ICH-induced iron toxicity causes WM injury through c-Jun N-terminal kinase (JNK) and receptor-interacting protein kinase 1 (RIPK1) activation. 7 Because of white matter's critical role in neurotransmission, WM injury may also lead to severe sensorimotor dysfunction, neurobehavioral impairment, and cognitive disorders.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…As the cell type that contains a high level of iron in the CNS, oligodendrocytes are very sensitive to iron overload and thus particularly susceptible to ICH injury. It has been reported that ICH induces oligodendrocyte death and demyelination in white matter, where functional and morphological maintenance is highly dependent on oligodendrocytes and their myelin sheaths …”
Section: Effects Of Ich On Oligodendrocyte‐lineage Cellsmentioning
confidence: 99%
“…It has been reported that ICH induces oligodendrocyte death and demyelination in white matter, 105,106 where functional and morphological maintenance is highly dependent on oligodendrocytes and their myelin sheaths. 107 How do oligodendrocytes die after ICH? On the one hand, there is evidence suggesting that apoptosis is responsible for oligodendrocyte death after ICH.…”
Section: Oligodendrocyte Death After Ichmentioning
confidence: 99%